2015
DOI: 10.3892/ijo.2015.2869
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechingallate induces apoptosis in B lymphoma cells via caspase-dependent pathway and Bcl-2 family protein modulation

Abstract: (−)-Epigallocatechingallate (EGCG) as a representative polyphenol has attracted increasing attention due to its diversified effects, especially its potential as an agent for the prevention or treatment of certain cancers. However, the molecular mechanisms of EGCG-induced apoptosis in B lymphoma cells are unclear. The aim of this study was to investigate the effect of EGCG on proliferation and apoptosis in the B lymphoma cell lines Jeko-1 and Raji, and determine the underlying mechanisms. Cell proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…In this study, we showed that EGCG decreased proliferation, induced apoptosis, and promoted differentiation in the promyelocytic leukemia cells via inhibition of MDR and PML‐RARα/HDAC1. EGCG was able to decrease the proliferation rate of APL cells, and this finding is consistent with previous reports on the growth inhibitory effect of EGCG in various cancer cells (Benyahia et al, ; Khan, Adhami, & Mukhtar, ; Ly et al, ; Wang et al, ). Although the obtained IC50 value for the antiproliferative effect of EGCG on leukemic cells was higher than that of ATRA, the antiproliferative effect was observed at concentrations with no obvious toxic effect on normal polymorphonuclear cells, suggesting the specificity of EGCG action in leukemic cells.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we showed that EGCG decreased proliferation, induced apoptosis, and promoted differentiation in the promyelocytic leukemia cells via inhibition of MDR and PML‐RARα/HDAC1. EGCG was able to decrease the proliferation rate of APL cells, and this finding is consistent with previous reports on the growth inhibitory effect of EGCG in various cancer cells (Benyahia et al, ; Khan, Adhami, & Mukhtar, ; Ly et al, ; Wang et al, ). Although the obtained IC50 value for the antiproliferative effect of EGCG on leukemic cells was higher than that of ATRA, the antiproliferative effect was observed at concentrations with no obvious toxic effect on normal polymorphonuclear cells, suggesting the specificity of EGCG action in leukemic cells.…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis is a complex process regulated by several molecules that function as either promoters, including Bax, Bak and caspases, or inhibitors of the cell death process such as Bcl-2, Bcl-xL and the IAP proteins (25). Studies have shown that EGCG can effectively regulate various key molecules in cell mitochondrial apoptosis pathways in other tumors as a potential antitumor substance (18,19). Our previous study showed that the long-term ingestion of green tea could effectively prevent lung cancer, in rats, induced by the carcinogen 3,4-benzopyrene (B[a]P), a process that may be related to the EGCG-mediated upregulation of P53 expression and downregulation of Bcl-2 expression (26).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has been demonstrated to act on multiple key elements in signal transduction pathways related to inhibition of carcinogen-induced mutagenesis (11,12), induction of cell cycle arrest (13), induction of apoptosis (14), inhibition of growth factor-mediated proliferation (15), inhibition of transformation (9), inhibition of angiogenesis (16) and inhibition of telomerase activity (17). It has been shown that EGCG can effectively regulate various key molecules in cell mitochondrial apoptosis pathways in other tumors as a potential antitumor substance (18,19). However, the molecular mechanisms of EGCG inducing apoptosis have not been completely elucidated in lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that EGCG is associated with the potential health benefits attributed to green tea consumption (21). The anticancer effect of EGCG has been explored in various tumor cells (22)(23)(24), but there are few articles concerning the anticancer effect of EGCG on esophageal cancer. In the present study, EGCG was demonstrated to suppress the viability of esophageal cancer Eca109 and Ec9706 cells via inducing apoptosis in an EGCG dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%